A comparison of long‐term changes in seismicity at The Geysers, Salton Sea, and Coso geothermal fields. Issue 1 (23rd January 2016) - Trugman, Daniel T.; Shearer, Peter M.; Borsa, Adrian A.; Fialko, Yuri
Abstract: Geothermal energy is an important source of renewable energy, yet its production is known to induce seismicity. Here we analyze seismicity at the three largest geothermal fields in California: The Geysers, Salton Sea, and Coso. We focus on resolving the temporal evolution of seismicity rates, which provides important observational constraints on how geothermal fields respond to natural and anthropogenic loading. We develop an iterative, regularized inversion procedure to partition the observed seismicity rate into two components: (1) the interaction rate due to earthquake‐earthquake triggering and (2) the smoothly varying background rate controlled by other time‐dependent stresses, including anthropogenic forcing. We apply our methodology to compare long‐term changes in seismicity to monthly records of fluid injection and withdrawal. At The Geysers, we find that the background seismicity rate is highly correlated with fluid injection, with the mean rate increasing by approximately 50% and exhibiting strong seasonal fluctuations following construction of the Santa Rosa pipeline in 2003. In contrast, at both Salton Sea and Coso, the background seismicity rate has remained relatively stable since 1990, though both experience short‐term rate fluctuations that are not obviously modulated by geothermal plant operation. We also observe significant temporal variations in Gutenberg‐Richter b value, earthquake magnitude distribution, and earthquake depth distribution, providing further evidence for the dynamic evolution of stresses within these fields. The differing field‐wide responses to fluid injection and withdrawal may reflect differences in in situ reservoir conditions and local tectonics, suggesting that a complex interplay of natural and anthropogenic stressing controls seismicity within California's geothermal fields. Key Points: We quantitatively compare changes in seismicity at The Geysers, Salton Sea, and Coso geothermal fields Fluid injection drives seasonal seismicity rate transients at The Geysers but not Salton Sea or Coso Each field exhibits significant changes in b value, magnitude distribution, and depth distribution